The mediating role of msme development in the relationship between productive zakat empowerment, mentoring, and mustahik welfare: evidence from PLS-SEM - Fitri Rorizki; Muhammad Habibi Siregar; Tri Inda Fadhila Rahma (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Productive zakat has been widely implemented to improve the economic welfare of mustahik through business capital assistance and mentoring. However, the effectiveness of these programs in enhancing welfare through the development of micro, small, and medium enterprises (MSMEs) has remained underexplored. This study examined the effects of productive zakat empowerment and mentoring on mustahik welfare, with MSME development as a mediating variable, at BAZNAS North Sumatra Province. A quantitative explanatory approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires, interviews, and documentation from 180 mustahik participating in the productive zakat program during 2020–2024. The findings indicated that productive zakat empowerment and mentoring had positive and significant effects on both MSME development and mustahik welfare. MSME development also had a positive and significant effect on mustahik welfare and partially mediated the relationships between productive zakat empowerment, mentoring, and welfare. These findings suggested that integrating productive zakat with sustainable mentoring and business development strategies could strengthen the long-term economic independence and welfare of mustahik.